NEWS PRESENTATION STYLE OF BERITAKITA ONLINE MAGAZINE PT. FREEPORT INDONESIA - Jeane Talakua; Ajel Christina (Media Inovasi Pendidikan dan Publikasi, 2024)
This writing uses a descriptive qualitative approach with primary and secondary data collected through observation, interviews, documentation, and literature review. The informants of this research came from the Corporate Communication Department which takes care of the company's communication activities including the creation of the internal magazine Berita Kita. The results showed that e-BeritaKita Online Magazine uses an issue selection style in the news and a news presentation and development style. Issues in news are defined as predictable events that involve various aspects of news. The magazine also applies the 5W+1H formula with follow-up news in its news presentation. In addition, evaluation is carried out to see whether the results that have been carried out are appropriate or not. This evaluation involves several indicators such as the number of visits, impressions, clicks, downloads, reading time, and feedback from readers. Surveys and interviews are also conducted with readers to find out their level of satisfaction, interest and preferences for the news presented. The goal is to always improve the quality and impact of the news presented in accordance with the goals and vision of the magazine.